The role of good governance in promoting effective municipal service delivery: a case of Thulamela Local Municipality - Phalanndwa, Ndamulelo (My University, 2025)
Good governance has become a focal point in academic discourse due to its critical role in enhancing living standards and fostering societal development. Ever since the present South African government acquired power in 1994, the government prioritised improved governance and service delivery, further making promises to transform the quality of citizens’ livelihood through effective and efficient service delivery. However, South African local municipalities experience critical service delivery problems due to poor governance and administration within their jurisdiction. The study aimed to investigate the role of good governance in promoting effective municipal service delivery and develop a framework that will be used to improve good governance and service delivery in Thulamela Local Municipality. The study adopted a mixedmethod approach for data collection to achieve the study's objectives. The convergent parallel mixed method approach was used. The reason for using the convergent parallel mixed method was to enable the researcher to merge or converge qualitative and quantitative data to provide a comprehensive analysis of the research problem. A total of 120 respondents were sampled. The sampling technique that was used to sample the study population is non-probability sampling with its sub-type purposive sampling technique. Data was collected using questionnaires and interviews. Quantitative data was analysed using statistical analysis through Statistical Package for Social Sciences (SPSS), Version 29.0. The data was presented in the form of tables, frequencies, and percentages. Qualitative data was analysed using NVivo version 14. The data was analysed using thematic analysis, whereby data collected through interviews were grouped into themes and presented in a narrative form. The findings of this study inform the strategies for enhancing good governance practices to improve municipal service delivery, potentially benefiting the broader community and similar municipalities. The Major findings of the study are: • There is a relationship between good governance practices and effective municipal service delivery. • Thulamela Local Municipality faces challenges such as the lack of public participation, poor infrastructure maintenance and poor responsiveness. • The Municipality has several initiatives, such as the Integrated Development Plan (IDP), Mayor-Mahosi and Imbizos, to promote effective municipal service delivery. • Involving the communities in decision-making enhances governance and municipal service delivery. The following recommendations are therefore made based on the findings of the study: • The study recommends that the Municipality implement stronger transparency measures, ensuring that all stakeholders have access to information regarding budget allocations, project timelines, and service delivery updates. • The Municipality should improve the implementation of the IDP by involving the community more actively in the formulation and review processes. • The study recommends that the Municipality encourages public participation through E-Participation so that community members can participate at the comfort of their homes. • The Municipality should strengthen the monitoring and evaluation mechanisms to improve service delivery.
M. Admin.
Department of Public and Development Administration
Keywords: Good governance; UCTD; Service delivery; Effectiveness; Local government; Thulamela Local Municipality